(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Staphylococcus aureus is common isolated pathogen from clinical specimen with increasing trend of antimicrobial resistance. Staphylococcus aureus and Coagulase-negative Staphylococci (CoNS) infections have become common among both hospitalized and non-hospitalized patients. Aim: The aim of this study was to determine the inducible clindamycin resistance among the MRSA and MSSA. Material and Method: This study was prospective study which includes the entire sample obtained in the Department of Microbiology laboratory from Tertiary Care Hospital with bacterial infection and confirmed by positive culture. The standard microbiological protocol for detection of inducible clindamycin, Disc approximation method (D–test) was performed. Result: Out of 124 Staphylococcus aureus isolates, 17 (13.7%) were inducible clindamycin resistant; 6 (35.29%) from (cefoxitin susceptible) MSSA and 11 (64.71%) from (cefoxitin resistance) MRSA. Conclusion: The incidence of inducible clindamycin resistance among the Staphylococcus aureus was high. This high rate screen among the MRSA and MSSA provokes the necessity of performing the D- test before starting the antibiotic therapy.